Home town story - Pierson, Arthur ([Place of publication not identified] [name of publisher not identified])
Home Town Story is a drama about a hard-hitting reporter fighting against political corruption. It's historically interesting because it shows Marilyn Monroe in one of her very early films, and heading for eventual immorality.
Alan Hale Jr., Marilyn Monroe, Jeffery Lynn.
Dolby digital.
In English.
Keywords: Political corruption; Immorality